2007
DOI: 10.1002/anie.200703759
|View full text |Cite
|
Sign up to set email alerts
|

Straightforward Synthesis of CF3‐Substituted Triarylethenes by Stereoselective Threefold Cross‐Coupling Reactions

Abstract: Any way round: The palladium‐catalyzed threefold cross‐coupling reaction of 1,1‐dibromo‐3,3,3‐trifluoro‐2‐tosyloxypropene with aryl boronic acids provides a versatile route to CF3‐substituted triarylethenes (see scheme). The CF3 group is essential for the high Z selectivity in the first coupling reaction, which is the key step in the process. Any of the ethene stereoisomers can be prepared simply by changing the order of the aryl boronic acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 44 publications
(8 reference statements)
0
16
0
Order By: Relevance
“…However, Takeda et al have reported the straightforward approach to the synthesis of CF 3 -substututed triarylethenes via three fold coupling reaction of 1-dibromo-3,3,3-trifluoro-2-tosyloxy-propene with boronic acid derivatives. [84] The first step of the synthesis involved the reaction tosylation of ketone derivative (372) with tosyl chloride in DCM to give 373 in 60% yield which was further reacted with boronic acid derivative (374) by using 5 mol% of [PdCl 2 (PPh 3 ) 2 ] and 5 mol% of P(m-tolyl) 3 in toluene at 80°C to give 375 in 94% yield with excellent E/Z ratio of 8/92. Compound 375 was further reacted with boronic acid (376) in toluene under basic conditions by using [Pd(PPh 3 ) 4 ] as catalyst to give single diastereomers of 377 in 88% yield.…”
Section: Formation Of Cà C Bondmentioning
confidence: 99%
“…However, Takeda et al have reported the straightforward approach to the synthesis of CF 3 -substututed triarylethenes via three fold coupling reaction of 1-dibromo-3,3,3-trifluoro-2-tosyloxy-propene with boronic acid derivatives. [84] The first step of the synthesis involved the reaction tosylation of ketone derivative (372) with tosyl chloride in DCM to give 373 in 60% yield which was further reacted with boronic acid derivative (374) by using 5 mol% of [PdCl 2 (PPh 3 ) 2 ] and 5 mol% of P(m-tolyl) 3 in toluene at 80°C to give 375 in 94% yield with excellent E/Z ratio of 8/92. Compound 375 was further reacted with boronic acid (376) in toluene under basic conditions by using [Pd(PPh 3 ) 4 ] as catalyst to give single diastereomers of 377 in 88% yield.…”
Section: Formation Of Cà C Bondmentioning
confidence: 99%
“…11 Shimizu and Hiyama have reported a more sophisticated application of the triple electrophilic vinyl tosylate S3-1 (Scheme S3). 12 The starting dibromovinyl tosylate S3-1 was coupled with arylboronic acids to afford the alkenes S3-2 in excellent isolated yields and with good stereoselectivities. 12 It has been suggested that the trans-stereoselectivity is the result of the Pd-F interaction during the cross-coupling reaction, which is represented by the structure S3-5.…”
Section: Cross-coupling Reactions Of Halovinyl Tosylatesmentioning
confidence: 99%
“…Br Br Approach for the synthesis of CF 3 -substituted triarylethenes (Simizu) 15 Stereoselective reaction of lithuim carbenoid with electrophiles (Lu) 14 up to 95% C. Approach for the synthesis of α -CF 3 α,β-unsaturated lactones (This work) Br Br …”
Section: Bmentioning
confidence: 99%
“…4: B). 15 Based on this knowledge, as reactions of fluorine-containing gem-dibromoalkenes usually provide Eproducts predominantly due to fluorine-metal interaction, the…”
Section: Introductionmentioning
confidence: 99%